Walking patterns - Ashari, Asmidawati; Tengku Abdul Hamid, Tengku Aizan; Hussain, Mohd Rizal (Universiti Putra Malaysia Press, 2016)
Balance is essential for mobility and performing activities of daily living. The ability to maintain balance during navigation in daily activities is a key component of successful ambulation. Gait and balance impairment have been consistently reported as among the strongest risk factors for falls among community dwelling seniors. Reduced coordination of postural control could lead to poor gait pattern and balance impairment among older people.